Holocene Surface Rupture History of an Active Forearc Fault Redefines Seismic Hazard in Southwestern British Columbia, Canada. Issue 21 (5th November 2018) - Morell, K. D.; Regalla, C.; Amos, C.; Bennett, S.; Leonard, L.; Graham, A.; Reedy, T.; Levson, V.; Telka, A.
Abstract: Characterizing the hazard associated with Quaternary‐active faults in the forearc crust of the northern Cascadia subduction zone has proven challenging due to historically low rates of seismicity, late Quaternary glacial scouring, and dense vegetation that often obscures fault‐related geomorphic features. We couple lidar topography with paleoseismic trenching across the Leech River Fault on southern Vancouver Island to produce the first detailed surface rupture history of an onland forearc fault in British Columbia, Canada. The results indicate that this fault produced three surface‐rupturing earthquakes in the last ∼9 kyr and is therefore capable of producing large ( M w >6) earthquakes in the future. We provide new constraints on the fault's length (∼130 km) and Holocene slip rate (≥0.2–0.3 mm/year) that, together with the earthquake ages, should be incorporated into new seismic hazard assessments and building code practices relevant to urban centers in southwestern British Columbia (Canada) and northwestern Washington State (United States). Plain Language Summary: In this study we document the first detailed history of earthquake surface rupture for an onland fault within the Cascadia subduction zone of British Columbia, Canada. We show that the Leech River Fault on southern Vancouver Island has produced three surface‐rupturing earthquakes in the last ∼9, 000 years and is therefore capable of producing large ( M > 6) earthquakes in the future. We provide new constraints on the fault's behavior that should be incorporated into new seismic hazard assessments and building code practices relevant to urban centers in southwestern British Columbia (Canada) and northwestern Washington State (United States). Nearby regions of SW British Columbia likely contain similar active faults that could host damaging earthquakes. Key Points: We present the first detailed surface rupture history of an onland forearc fault in British Columbia, Canada The Leech River Fault produced three surface‐rupturing earthquakes in the last ∼9 kyr and is capable of producing large earthquakes The Canadian forearc likely contains additional active crustal faults that could host damaging surface‐rupturing earthquakes